2017
DOI: 10.1002/osp4.144
|View full text |Cite
|
Sign up to set email alerts
|

A new method to visualize obesity prevalence in Seattle‐King County at the census block level

Abstract: Summary ObjectiveThe aim of this study is to map obesity prevalence in Seattle King County at the census block level. MethodsData for 1,632 adult men and women came from the Seattle Obesity Study I. Demographic, socioeconomic and anthropometric data were collected via telephone survey. Home addresses were geocoded, and tax parcel residential property values were obtained from the King County tax assessor. Multiple logistic regression tested associations between house prices and obesity rates. House prices aggr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 14 publications
(23 reference statements)
0
10
0
Order By: Relevance
“…They may capture net worth and SES more consistently and with a clearer gradient than either self-reported educational attainment or household incomes (Lovasi et al, 2012, Rundle et al, 2013, Duncan et al, 2005, Fiechtner et al, 2013, Duncan et al, 2012, Rundle et al, 2011, Wall et al, 2012, Dunton et al, 2009, Auchincloss et al, 2009). In past studies, key characteristics of “obesogenic” neighborhoods were associated with lower property values (Drewnowski et al, 2014, Drewnowski et al, 2018, Drewnowski et al, 2016b).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…They may capture net worth and SES more consistently and with a clearer gradient than either self-reported educational attainment or household incomes (Lovasi et al, 2012, Rundle et al, 2013, Duncan et al, 2005, Fiechtner et al, 2013, Duncan et al, 2012, Rundle et al, 2011, Wall et al, 2012, Dunton et al, 2009, Auchincloss et al, 2009). In past studies, key characteristics of “obesogenic” neighborhoods were associated with lower property values (Drewnowski et al, 2014, Drewnowski et al, 2018, Drewnowski et al, 2016b).…”
Section: Discussionmentioning
confidence: 99%
“…Each SOS participant completed a general-select (G-SEL) version of the validated (Neuhouser et al, 1999, Patterson et al, 1999, Kristal et al, 2000) FFQ. This FFQ has been widely used in health studies in the past (Drewnowski et al, 2016a, Drewnowski et al, 2018, Neuhouser et al, 1999, Patterson et al, 1999, Kristal et al, 2000, Lippman et al, 2005, Masset et al, 2009). The G-SEL is a semi-quantitative FFQ, collecting information on both frequency (with response categories ranging from “never or less than once per month” to “2+ times per day”) and portion size (small, medium, and large) for 125 food items.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The RLF overcomes other problems related to aggregated spatial data obtained from census and other governmental statistics that are available only for predefined administrative areas, which can yield results tainted with the modifıable areal unit problem (Vernez Moudon et al ., ). Based on local property sales data, the RLF has a further benefit as a composite measure of wealth potentially reducing measurement error, co‐linearity, and over‐adjustment in analysis and conferring ease of explanation (Drewnowski et al ., ; Feng et al ., ). Property values have been found to be a stronger predictor of health over traditional measures of SES (Rehm et al ., ; Vernez Moudon et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…In Australian adults, greater increases in weight [5,30] and waist girth have been observed for people in areas with greatest area-level socioeconomic disadvantage [5]. Recent studies have also included residential property values in the features of physical built environment to derive indices of both individual-level and area-level SES [31][32][33][34]. Studies showed that lower property values were linked to higher BMI and higher risk of obesity [8,9,34] as well as to higher cardiometabolic risks [31,35].…”
Section: Introductionmentioning
confidence: 99%